Structure and properties of iron shot heat-treated during induction heating, produced at MAZ - P. S. Gurchenko; M. I. Demin; N. A. Simonov; D. A. Volkov; V. L. Rassudov (Литьë и металлургия, 2001)
The investigation results of structure and properties of iron shot of MAZ production in as-cast condition and after tempering during induction heating to 280—450 °C are presented. It is shown that during induction heating tempering processes run completely during 5—7minutes' heating. Due to tempering, in purification operations durability raises by 3—5 times.